Pengaruh Human Development Index (HDI) Terhadap Pertumbuhan Ekonomi Luwu Raya - Mustain, Ainul; Patra, I Ketut; Maming, Rian (Universitas Nusantara PGRI Kediri, 2023)
Economic growth is the process of increasing a country's capacity to produce goods and services, which are part of long-term economic activity. One of indicators that can support increasing economic growth in a region is the human development index. The purpose of this research is to find out the impact of the Human Development Index on Economic Growth in Luwu Raya. The data used is a ten year time series data. The data were obtained from the Luwu Raya Central Statistics Agency which provided data on the Human Development Index and Economic Growth for 2011 - 2020. In this research, simple linear regression analysis method was used to process data through SPSS version 20. The test results showed that the coefficient of the independent variable was 0.257 or 25,7%. It can be said that the dependent variable was influenced by independent variables, and 74,3 percent of the variables were influenced by other variables not related to the research. Human Development Index and Economic Growth was not effect on the relationship between variables. Economic Growth will increase by 50,7 percent for every 1% increase in the Human Development Index. It is expected that the government of Luwu Raya can implement appropriate policies to improve the quality of the Human Development Index, so it can promote economic growth based on the findings of this study.